Late Mesozoic adakite granites of the southern frame of the eastern flank of the Mongol-Okhotsk orogenic belt: material composition and geodynamic conditions of formation - I. M. Derbeko; A. V. Chugaev (Геодинамика и тектонофизика, 2020)
Granitoids of the Magdagachi complex were studied using new and published petrochemical, geochemical and isotopic (Sm-Nd, Rb-Sr) data. Granitoid samples were taken from the southern frame of the eastern flank of the Mongol-Okhotsk orogenic belt (MOOB). Their analysis shows increased concentrations of Sr, Ba, Eu; reduced concentrations of Nb, Ta; abnormally low concentrations of HREE, Y and Yb; significant fractionation of REE; and high Sr/Y ratios. Therefore, the Magdagachi granitoids are "classical" adakites that may have formed at a depth of more than 45 km due to melting of eclogite with a garnet content of 20–50 %. Such conditions could exist under subduction as a result of melting of the frontal or lateral parts of the slab in subduction windows formed during oblique subduction at an orthogonal sinking angle. Highly metamorphosed lower crust Precambrian formations were also melted, and a source of parental melts could have been composed of both the mantle and crustal materials. Two tectonic scenarios are proposed that could have been accompanied by the formation of Magdagachi granitoids. Both scenarios refer to subduction processes, but differ in interactions between various regional structures in the Late Mesozoic.